Codon-Optimized Luciferase Variants for Mammalian Gene Expression in Culture and in Vivo - Casey A. Maguire; Johannes C. van der Mijn; Marja H. Degeling; Danielle Morse; Bakhos A. Tannous (Molecular Imaging)
Luciferases have proven to be useful tools in advancing our understanding of biologic processes. Having a multitude of bioluminescent reporters with different properties is highly desirable. We characterized codon-optimized thermostable green- and red-emitting luciferase variants from the Italian firefly Luciola italica for mammalian gene expression in culture and in vivo. Using lentivirus vectors to deliver and stably express these luciferases in mammalian cells, we showed that both variants displayed similar levels of activity and protein half-lives as well as similar light emission kinetics and higher stability compared to the North American firefly luciferase. Further, we characterized the red-shifted variant for in vivo bioluminescence imaging. Intramuscular injection of tumor cells stably expressing this variant into nude mice yielded a robust luciferase activity. Light emission peaked at 10 minutes post-D-luciferin injection and retained > 60% of signal at 1 hour. Similarly, luciferase activity from intracranially injected glioma cells expressing the red-shifted variant was readily detected and used as a marker to monitor tumor growth over time. Overall, our characterization of these codon-optimized luciferases lays the groundwork for their further use as bioluminescent reporters in mammalian cells.